Inactivation of Serotonergic Neurons in the Rostral Medullary Raphé Attenuates Stress-Induced Tachypnea and Tachycardia in Mice - Ikoma, Yoko; Kusumoto-Yoshida, Ikue; Yamanaka, Akihiro; Ootsuka, Youichirou; Kuwaki, Tomoyuki (Frontiers in Physiology, 2018)
The medullary raphé nuclei are involved in controlling cardiovascular, respiratory and thermoregulatory functions, as well as mediating stress-induced tachycardia and hyperthermia. Although the serotonergic system of the medullary raphé has been suggested as the responsible entity, specific evidence has been insufficient. In the present study, we tested this possibility by utilizing an optogenetic approach. We used genetically modified mice (Tph2; ArchT mice) in which archaerhodopsin-T, a green light-driven neuronal silencer, was selectively expressed in serotonergic neurons under the regulation of tryptophan hydroxylase 2 promoters. We first confirmed that an intruder stress selectively activated medullary, but not dorsal or median raphé serotonergic neurons. This activation was suppressed by photo-illumination via a pre-implanted optical fiber, as evidenced by the decrease of a cellular activation marker protein in the neurons. Next, we measured ECG, respiration, body temperature, and locomotor activity in freely moving mice during intruder and cage-drop stress tests, with and without photo-illumination. In the intruder test, photo inactivation of the medullary serotonergic neurons significantly attenuated tachycardia (362±58 vs. 564±65 bpm•min, n=19, p=0.002) and tachypnea (94±82 vs. 361±138 cpm•min, n=9, p=0.026), but not hyperthermia (1.0±0.1 vs. 1.0±0.1 °C•min, n=19, p=0.926) or hyperlocomotion (17±4 vs. 22±4, arbitrary, n=19, p=0.089). Similar results were obtained from cage-drop stress testing. Finally, photo-illumination did not affect the basal parameters of the resting condition. We conclude that a subpopulation of serotonergic neurons in the medullary raphé specifically mediate stress-induced tachypnea and tachycardia, which have little involvement in the basal determination of respiratory frequency and heart rate, specifically mediate stress-induced tachycardia and tachypnea.